Coping mechanisms among Palestinian refugee families in Malaysia during the transition period - Eid, Iyad Muhammad; Mohamad Diah, Nurazzura (Emerald Group Publishing Limited, 2019)
Purpose – The purpose of this paper is to explore how Palestinian refugee families in Malaysia cope with the challenges they face during their transitional destination. These families have recently fled from conflict zones in various Arab countries and moved to Malaysia where they registered in the office of the United Nations High Commissioner for Refugees (UNHCR) in Kuala Lumpur, waiting for resettlement in a third country. Design/methodology/approach – The paper utilizes the qualitative research approach, drawing descriptive analysis (thematic analysis technique) of data collected by semi-structured, in-depth interviews with 30 Palestinian families. For sample selection, the author used purposive sampling and employed the Snowball technique to select the families who have experienced refuge life for the second time. Then the sample was equally divided into three groups to include ten families moving from Iraq, Syria and the Gaza Strip. The interviews were conducted with the head of the families who varied in terms of gender and age composition. The study involved 9 female participants and 21 males. They are all Muslims and aged between 24 and 80 years old. In terms of educational background, all of the participants are literate with formal school education, diploma or tertiary education. Findings – The study shows that refugee families adopt four main ways of coping commonly used to improve the quality of their life during their transition in Malaysia. They turn to religion and spirituality, keep in touch with relatives and friends in the diaspora and conflict zones, develop a positive image about their present situation by comparing it to worse living conditions of others living in conflict zones and plan to migrate to Europe to hold a European passport which will give them the opportunity to visit their original country, Palestine. Originality/value – The paper tackles the Palestinian refugee family life and explores their real-life stories and experiences during transition in Malaysia. It provides them with an opportunity to speak up their suffering and reveal the various strategies they adopt to cope with life challenges. Besides, the result of the study will be a fruitful addition to the corpus of sociological knowledge as well as an important contribution to the families that stay in transition in different societies around the world.